2016
DOI: 10.1038/srep19427
|View full text |Cite|
|
Sign up to set email alerts
|

The genome sequence of the outbreeding globe artichoke constructed de novo incorporating a phase-aware low-pass sequencing strategy of F1 progeny

Abstract: Globe artichoke (Cynara cardunculus var. scolymus) is an out-crossing, perennial, multi-use crop species that is grown worldwide and belongs to the Compositae, one of the most successful Angiosperm families. We describe the first genome sequence of globe artichoke. The assembly, comprising of 13,588 scaffolds covering 725 of the 1,084 Mb genome, was generated using ~133-fold Illumina sequencing data and encodes 26,889 predicted genes. Re-sequencing (30×) of globe artichoke and cultivated cardoon (C. cardunculu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
111
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 103 publications
(118 citation statements)
references
References 74 publications
6
111
1
Order By: Relevance
“…DNA transposons were annotated with a custom pipeline that includes the 'gt tirvish' command, which is part of the GenomeTools suite 42 . The age of LTR-RTs was determined by obtaining a likelihood divergence estimate between the LTRs with baseml from PAML 43 16 , coffee 17 and lettuce 15 and with grape 18 as the outgroup. Identification of orthology and paralogy relationships, measurements of sequence divergence and estimation of divergence time through the level of synonymous substitutions were performed as detailed in Supplementary Note 3.1 on the basis of the methods described in ref.…”
Section: Letter Research Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…DNA transposons were annotated with a custom pipeline that includes the 'gt tirvish' command, which is part of the GenomeTools suite 42 . The age of LTR-RTs was determined by obtaining a likelihood divergence estimate between the LTRs with baseml from PAML 43 16 , coffee 17 and lettuce 15 and with grape 18 as the outgroup. Identification of orthology and paralogy relationships, measurements of sequence divergence and estimation of divergence time through the level of synonymous substitutions were performed as detailed in Supplementary Note 3.1 on the basis of the methods described in ref.…”
Section: Letter Research Methodsmentioning
confidence: 99%
“…Flowering time genes in A. thaliana were retrieved from a recently developed database, FLOR-ID 20 , which includes 295 protein-coding genes and 11 miRNA genes and describes their interactions. We built gene clusters for a set of seven species, namely H. annuus, A. thaliana, Cynara cardunculus, Oryza sativa, Hordeum vulgare, Brassica rapa and Populus trichocarpa, chosen to be consistent with a previous study that identified orthologues for more than 30 flowering-time genes in the sunflower 21 , adding the proteome of the recently sequenced member of Asterids II C. cardunculus 16 . To identify orthologues and in-paralogues (that is, paralogues post-dating speciation) of A. thaliana genes, we built and visually examined trees for the clusters defined above (Supplementary Note 6.2) and manually screened BLAST reports on the sunflower genome browser.…”
Section: Letter Research Methodsmentioning
confidence: 99%
See 3 more Smart Citations